Fondements économiques de la réflexion du xviiie siècle autour de l’homme porteur de droits - Manuela Albertone (Clio@Themis)
According to a political investigation of the Physiocracy, this article aims at highlighting the economic foundations of the 18th century French discourse on rights and its gender implications, developed particularly by Condorcet, one of the French revolutionary leaders close to the Physiocracy. By this perspective, the author offers a new reading of Physiocratic political rationalism and of its contribution to the Déclaration des droits de l’homme. Combining this approach with his democratic faith, Condorcet attained to reject any political difference among men and women.